The Combination of Anti‐NKG2D and CTLA‐4 Ig Therapy Prolongs Islet Allograft Survival in a Murine Model. Issue 10 (1st September 2014) - Pawlick, R.; Gala‐Lopez, B.; Pepper, A. R.; McCall, M.; Ziff, O.; Shapiro, A. M. J.
<x xml:space="preserve">Abstract</x> Islet transplantation is an effective means of treating severe type 1 diabetes in patients with life‐threatening hypoglycemia. Improvements in glycemic control with correction of HbA1C enhance quality of life irrespective of insulin independence. By antagonizing the Natural Killer Group 2, member D (NKG2D) receptor expression on NK and CD8+ T cells, in combination with blocking CTLA‐4 binding sites, we demonstrate a significant delay of graft rejection in islet allotransplant. Anti‐NKG2D combined with CTLA‐4 Ig (n = 15) results in prolonged allograft survival, with 84.6 ± 10% of the recipients displaying insulin independence compared to controls (n = 10, p < 0.001). The effect of combination therapy on graft survival is superior to treatments alone (CTLA‐4 Ig vs. combination p = 0.024, anti‐NKG2D vs. combination p < 0.001) indicating an interaction between these pathways. In addition, combination treatment also improves glucose tolerance when compared to controls (n = 10, p = 0.018). Histologically, NKG2D+ cells were significantly decreased within the allograft after 7 days of combination treatment (n = 6, p = 0.029). T cell proliferation was significantly reduced with anti‐NKG2D therapy and CD8+ T cell daughter fractions were also significantly decreased with mAb and combination treatment when measured by in vitro mixed lymphocyte reaction (n = 5, p = 0.015, p = 0.005 and p = 0.048). These results demonstrate that inhibition of NKG2D receptors and costimulatory pathways enhance islet allograft survival.